Hackett, Lionel (London, 2013)
2013 "Hackett, Lionel", 2013, HistoryTalk Lionel arrived in England from Barbados in March 1957. He got a job on London Transport after being recruited in Barbados and started work at the Isleworth Trolley Depot. He received two weeks training at Chiswick Works including operating the Gibson ticket machine. He worked for two- three years as a conductor and then began driving trolley buses. He lived in Shepherds Bush and would travel to Isleworth on the staff train from Hammersmith.Broadway. He describes the shift system and working day. He worked for London Transport until 1969 and then moved to the Post Office. He recalls the working conditions in the Post Office when he worked as a postman in north- west London. He wanted to study motor mechanics and trained in this field in Enfield for six months after leaving the Post Office, then at Paddington Technical College and received the Royal Transport Engineer Certificate. He notes that he always to improve himself and further his education. He later worked for London transport again, at Westbourne Park garage as an engineer repairing buses in the 1980s until retirement in 2000.